Accumulation of amyloid beta (Aβ) and amyloid precursor protein (APP) in tumors formed by a mouse xenograft model of inflammatory breast cancer. Issue 1 (26th October 2021) - Zayas‐Santiago, Astrid; Martínez‐Montemayor, Michelle M.; Colón‐Vázquez, Jadier; Ortiz‐Soto, Gabriela; Cirino‐Simonet, Jose G.; Inyushin, Mikhail
Abstract : Accumulation of amyloid in breast cancer is a well‐known phenomenon, but only immunoglobulin light‐chain amyloidosis (AL) or transthyretin (TTR) amyloid had been detected in human breast tumor samples previously. We recently reported that another amyloidogenic peptide, amyloid beta (Aβ), is present in an aggregated form in animal and human high‐grade gliomas and suggested that it originates systemically from the blood, possibly generated by platelets. To study whether breast cancers are also associated with these Aβ peptides and in what form, we used a nude mouse model inoculated with triple‐negative inflammatory breast cancer cell (SUM‐149) xenografts, which develop noticeable tumors. Immunostaining with two types of specific antibodies for Aβ identified the clear presence of Aβ peptides associated with (a) carcinoma cells and (b) extracellular aggregated amyloid (also revealed by Congo red and thioflavin S staining). Aβ peptides, in both cells and in aggregated amyloid, were distributed in clear gradients, with maximum levels near blood vessels. We detected significant presence of amyloid precursor protein (APP) in the walls of blood vessels of tumor samples, as well as in carcinoma cells. Finally, we used ELISA to confirm the presence of elevated levels of mouse‐generated Aβ40 in tumors. We conclude that Aβ in inflammatory breast cancer tumors, at least in a mouse model, is always present and is concentrated near blood vessels. We also discuss here the possible pathways of Aβ accumulation in tumors and whether this phenomenon could represent the specific signature of high‐grade cancers. Abstract : Aβ (amyloid beta) and it's precursor APP can be observed in tumors formed by mouse xenograft model of human inflammatory breast cancer (IBC). Aβ is present in and around carcinoma cells and is concentrated near blood vessels. We suggest that systemic Aβ from mouse blood and/or vessels (containing amyloid precursor APP) may be, jointly with other amyloidogenic peptides, forming aggregated amyloid in these tumors.